Offline web applications in HTML5 - Griffiths, David 1969- (O'Reilly Media, 2010)
"Although HTML5 has a ton of bells and whistles, it's very much an integral part of the coming Web, and not everything about it is flashy and sexy. HTML5 actually offers a lot in terms of enhancing your web forms. Further, you can now build applications that function when your users aren't connected to a network. This Breakdown teaches you how to build 21st century forms: they'll validate your data, respond to data type mistakes, and even keep working when the WiFi goes down."--Resource description page.
Keywords: HTML (Document markup language); Application software -- Development; Mobile computing; HTML (Langage de balisage); Logiciels d'application; Développement; Informatique mobile; HTML; Application software; Development